Peningkatan Keterampilan Keamanan Digital pada Siswa SMK Ananda Bekasi di Era Disrupsi Digital - Nurul Hidayat; Nalendra Paccagnnelae; Damiara Paramithaswari (Jurnal Pengabdian Masyarakat Waradin, 2024)
The current era of digital disruption is a challenge in itself with the development of digitalization issues that have an impact on all aspects of life. Digital disruption brings significant changes in various aspects of life, including in the field of education. SMK Ananda Bekasi, as a vocational education institution, needs to prepare its students to be able to face increasingly complex digital security challenges. This research aims to improve digital security skills in SMK Ananda Bekasi students through a specially designed training program. The methods used in this community service include needs analysis, design of training materials, and evaluation of training results The results of this community service show that digital security skills improvement training has a positive impact in increasing students' awareness and ability to deal with cyber threats. Thus, this training program is expected to be a model for other schools in improving digital literacy and cybersecurity among students.